Converting Alkali Lignin to Biofuels over NiO/HZSM‐5 Catalysts Using a Two‐Stage Reactor. Issue 6 (11th May 2017) - Cheng, Shouyun; Wei, Lin; Zhao, Xianhui; Julson, James; Kadis, Ethan
Abstract: A series of NiO/HZSM‐5 catalysts were used to convert alkali lignin to hydrocarbon biofuels in a two‐stage catalytic pyrolysis system. The results indicated that all NiO/HZSM‐5 catalysts reduced the content of undesirable phenols, furans, and alcohols of the biofuel compared to non‐catalytic treatment. The NiO/HZSM‐5 catalyst with the lowest amount of NiO generated the highest biofuel yield in all catalytic treatments, and it also produced biofuel with the highest content of hydrocarbons. The emission of carbon oxides (CO and CO2 ) increased in the treatments with higher‐NiO loading HZSM‐5 due to the redox reaction between NiO and the oxygenated compounds in the bio‐oil. Ni2 SiO4 was generated in the used NiO/HZSM‐5 catalysts during the high‐temperature pyrolysis process. Abstract : Waste alkali lignin derived from black liquor in the pulp and paper industry can be converted to valuable hydrocarbon biofuel products through catalytic pyrolysis in a two‐stage reactor. The reactor can reduce the catalyst consumption, and the investigated NiO/HZSM‐5 catalyst is shown to be a promising catalyst candidate with higher activity and stability compared to pure HZSM‐5.